Modern macroeconomics : its origins, development and current state - Snowdon, Brian; Vane, Howard R. (Cheltenham, UK ; Northhampton, MA : E. Elgar, 2005)
The authors trace the origins, development and current state of modern macroeconomics from an historical perspective. They do so by thoroughly appraising the central tenets underlying the main competing schools of macroeconomic thought as well as their diverse policy implications.
Includes bibliographical references (p. 708-790) and indexes.
oif 27/04/15
Loan
Keywords: Macroeconomics; Keynesian economics; Comparative economics